Evaluating the Necessity to Perform Histopathologic Examination in Routine Tonsillectomy Specimens - Nepali, Rajendra; Dubey, Tulika; KC, Neeraj; Poudel, Suman; Gurung, Banita (Journal of College of Medical Sciences-Nepal, 2021)
Background Tonsillar diseases are common in adults and pediatric populations, and tonsillectomy is the most frequently performed surgery by Otolaryngology, Head and Neck surgeons. There is controversy over whether regular tonsillectomy specimens require histopathological examination. Healthcare resources conduct microscopic and histopathologic investigations so that malignancy is not missed and to prevent medicolegal proceedings. The purpose of this study is to ascertain whether a histological investigation of the removed tonsils is required or not. Methods A four-year retrospective chart review of adult and child patients who underwent tonsillectomies at the Department of Otolaryngology, Head, and Neck Surgery at Gandaki Medical College Teaching Hospital and Research center, Pokhara, Nepal, from January 2018 to December 2021 was included. The study sample included 173 patients whose postoperative tonsil specimens were routinely sent for histopathological evaluation to diagnose unexpected malignancy. Non-routine indications for tonsillectomy surgery were not included in our analysis. The data obtained included biodata and histopathological diagnoses. Results Among the 173 patients who met our inclusion criteria, 16(9.2%) were children and 157(90.8%) were adults. There were 63(36.4%) males and 110(63.6%) females. The histopathological diagnosis was chronic tonsillitis with hyperplasia (39.3%), chronic tonsillitis (26%), follicular tonsillitis (18.5%), and chronic suppurative tonsillitis (16.2%). Conclusions In the absence of risk factors, malignancy in excised tonsils is very rare; therefore, routine histopathological assessment is not necessary. This will help to escape the financial burden for patients and the waste of pathologists’ time.